Pengaruh Kecerdasan Emosi terhadap Motivasi Belajar Siswa Kelas 12 SMA N 1 Lubuk Alung - Iswandi, Firenia Aprilaniki; Meihana, Azizah; Samiana, Aulia; Fanesha, Rizkiqa Tria; Hamama, Dian; Rahayu, Wirza Feny (Lembaga Yasin AlSys, 2025)
This study examines the influence of Emotional Quotient (EQ) on students' learning motivation among 12th-grade students at SMA N 1 Lubuk Alung. Employing a quantitative correlational research design, the study involved 175 students selected through simple random sampling. Data were collected using the Emotional Intelligence Scale by Suryati (2024) and the Learning Motivation Scale by Iqbal (2023). The analysis revealed a significant positive relationship between emotional intelligence and learning motivation (p < 0.001, R = 0.610). Findings suggest that higher emotional intelligence is associated with greater learning motivation. The study emphasizes the importance of emotional intelligence in enhancing academic motivation, with practical recommendations for educators and policymakers to integrate emotional intelligence development into educational practices.